Genomic and biological study of fusion genes as resistance mechanisms to EGFR inhibitors - Kobayashi Yoshihisa; Oxnard Geoffrey R.; Cohen Elizabeth F.; Mahadevan Navin R.; Alessi Joao V.; Hung Yin P.; Bertram Arrien A.; Heppner David E.; Ribeiro Mauricio F.; Sacardo Karina P.; Saddi Rodrigo; Macedo Mariana P.; et al. (NATURE PORTFOLIO, 2022)
The clinical significance of gene fusions detected by DNA-based next generation sequencing remains unclear as resistance mechanisms to EGFR tyrosine kinase inhibitors in EGFR mutant non-small cell lung cancer. By studying EGFR inhibitor-resistant patients treated with a combination of an EGFR inhibitor and a drug targeting the putative resistance-causing fusion oncogene, we identify patients who benefit and those who do not from this treatment approach. Through evaluation including RNA-seq of potential drug resistance-imparting fusion oncogenes in 504 patients with EGFR mutant lung cancer, we identify only a minority of them as functional, potentially capable of imparting EGFR inhibitor resistance. We further functionally validate fusion oncogenes in vitro using CRISPR-based editing of EGFR mutant cell lines and use these models to identify known and unknown drug resistance mechanisms to combination therapies. Collectively, our results partially reveal the complex nature of fusion oncogenes as potential drug resistance mechanisms and highlight approaches that can be undertaken to determine their functional significance.